2017
DOI: 10.1073/pnas.1719109115
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal delivery of Hedgehog directs spatial patterning of taste organ regeneration

Abstract: How organs maintain and restore functional integrity during ordinary tissue turnover or following injury represents a central biological problem. The maintenance of taste sensory organs in the tongue was shown 140 years ago to depend on innervation from distant ganglion neurons, but the underlying mechanism has remained unknown. Here, we show that Sonic hedgehog (Shh), which encodes a secreted protein signal, is expressed in these sensory neurons, and that experimental ablation of neuronal Shh expression cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
89
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(98 citation statements)
references
References 48 publications
8
89
1
Order By: Relevance
“…However when HPI treatment is discontinued, the TB return/regenerate in FP and CV in mouse 3 . We and others have shown that GG neurons and nerve fibers are a source of SHH in taste organs 3 , 21 , 35 . We also reported that after HPI, SHH+ expression remained in the GG soma and furthermore, after HPI there was no decrease in numbers of GG neurons that express SHH 3 .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…However when HPI treatment is discontinued, the TB return/regenerate in FP and CV in mouse 3 . We and others have shown that GG neurons and nerve fibers are a source of SHH in taste organs 3 , 21 , 35 . We also reported that after HPI, SHH+ expression remained in the GG soma and furthermore, after HPI there was no decrease in numbers of GG neurons that express SHH 3 .…”
Section: Discussionmentioning
confidence: 80%
“…2a , K18/Ki67). Because HH regulation of proliferation in mouse FP has been reported 3 , 21 we counted Ki67+ cells in FP apical and basal wall regions (Fig. 2a , Vehicle).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurally supplied SHH is not required for taste progenitor activation. In adult tongue, SHH is expressed by postmitotic taste precursor cells and gustatory sensory neurons of the VII th cranial ganglion, which together support continual TRC differentiation (Castillo-Azofeifa et al, 2017;Lu et al, 2018;Miura et al, 2003). However, embryonic taste placodes are not innervated at specification, hence the only early source of lingual SHH is placodal (Hall et al, 1999).…”
Section: Embryonic Shh+ Taste Placodes and Postnatal Krt14+ Progenitomentioning
confidence: 99%
“…In adult tongue, by contrast, SHH promotes TRC differentiation. Genetic deletion or pharmacological inhibition of Hh pathway components in mice inhibits taste cell differentiation (Castillo-Azofeifa et al, 2017;Castillo-Azofeifa et al, 2018;Kumari et al, 2015;Lu et al, 2018), while forced SHH expression induces formation of ectopic taste buds comprising all 3 TRC types (Castillo et al, 2014).…”
Section: Embryonic Shh+ Placodes and Postnatal Krt14+ Progenitors Givmentioning
confidence: 99%